Deciphering the fate of sulfate in one- and two-chamber bioelectrochemical systems. (10th March 2022) - Dai, Shixiang; Korth, Benjamin; Schwab, Laura; Aulenta, Federico; Vogt, Carsten; Harnisch, Falk
Highlights: Sulfate reduction in one- and two-chamber BES was evaluated. Two-chamber BES showed 9.7 ± 2.6 mg L −1 d −1 cm −2 SRR and 83.9 ± 1.3% ER sulfate . Apparently no sulfate reduction was observed in one-chamber BES. Desulfomicrobium and Desulfovibrio dominated microbial community in two-chamber BES. Abstract: Treatment of wastewaters with high concentration of sulfate before discharge is an environmental imperative. However, current technologies are often highly energy- and chemical-demanding. Recently, microbial electrochemical technologies (MET) have been proposed as an alternative and more sustainable approach for the treatment of wastewaters rich in sulfate. Here we compare the sulfate reduction performance of one- and two-chamber reactors. In two-chamber reactors, sulfate reduction to sulfide was achieved with high electron recovery efficiency (83.9 ± 1.3%) at a sulfate reduction rate of 9.7 ± 2.6 mg SO4 2− L −1 d −1 cm −2, whereas in one-chamber reactors apparently no sulfate reduction took place. Non-electrochemical microcosm experiments suggested that sulfate reduction in two-chamber reactors was driven by the availability of cathodically produced H2 . In one-chamber reactors, the presence of anodically produced O2 presumably resulted in chemical short circuit including aerobic hydrogen oxidation, abiotic and biotic re-oxidation of sulfide to sulfate. Microbial community analysis demonstrated that sulfate reduction was mainly performed by sulfate reducing prokaryotes (SRP) belonging to the genera Desulfomicrobium and Desulfovibrio, whereas sulfide oxidizing bacteria (SOB) (mainly Acinetobacter and Sulfuricurvum ) could be responsible for re-oxidation of sulfide. Thus, fundamental and application-oriented research on microbial electrochemical sulfate reduction ought to be studied in two-chamber reactors for avoiding a potential bias of results by anodic reactions. Graphical abstract: Image, graphical abstract